Invigilation scheduling management system (ISMS) / Rahmat Sharifuddin Saari - Rahmat Sharifuddin, Saari (2016)
This project is about developing Invigilation Scheduling Management System (ISMS) that automate the process of determination the invigilators using rule-based and case-based. Based on an existing system in UiTM Perak, called E-Pengawasan \Peperiksaan, many problems occurred regarding the process times, data management, and constraint element could not being handle carefully and crucial. There exists some of critical information could not be handled properly that can cause misinformation and disturbance to administration and invigilators technically. The data and information in this system are being handled with a lot of process. Then as the project proposed, it will improve on those technical aspects. It adds a few functions that are suitable and reliable to users using a few improvement including rule-based and case-based reasoning. It is a hybrid Artificial Intelligence technique and utilizing a web-based system as the platform. This project concentrates on constructing a system for examination committee and providing information for invigilators in UiTM Sri Iskandar, Perak. The requirements of determine invigilators are referred to the rules provided by UiTM Sri Iskandar, Perak. This system when complete, it can be used by examination committee to manage all examination process faster, efficient and effective. The number of staffs involved will be reduced thus minimal human error and system will automatically process all the data to provide accurate and reliable data.